(untitled) (Педагогіка вищої та середньої школи, 2006)
The definition of “need” and its place in student’s professional activity in higher educational establishment is studied in this work. The survey of having scientific researches in this field applied to pedagogy, psychology and philosophy is made. The analysis of works let us affirm that the definition “need” is one of the main definitions in theory of person development. In its turn, the highest constituent of definition of “need ” is the definition “need of self-realization in professional activity”. An insufficient research of these definitions in the context of professional activity of students gives the reasons for further learning and analyzing of this problem. It was learned that the definitions “need” and “self realization” have the qualities characterizing the forms of man’s growth to personal and professional maturity.